Different shape of vias used on substrate integrated waveguide / Muhammad Hafidzi Zulkarnain - Zulkarnain, Muhammad Hafidzi (2016)
Recently, there has been a lot of interest in the substrate integrated waveguide (SIW) technology concept allowing the integration of waveguides in the substrate, replacing the rectangular metal waveguide sidewalls by two rows of metal rods. For the next coming decade SIW technology is the most potential candidate for the implementation of millimeter-wave (mm-wave) integrated circuits. In this paper, the design and modeling of SIW using different vias has been analyzed and designed to investigate the effect of changing shape of vias on the SIW on its operating parameters. Parameters that have been evaluated in these works are electric field, return losses and the transmission gain. The Ku-band SIW is conceived. FR4 is used as a dielectric substrate to evaluate the results in the frequency domain at 12 GHz. The circuit has been designed using finite element method based design software and simulated in HFSS software